2016
DOI: 10.3390/en9121044
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Mitigation for High Frequency Switching Transients Due to Energization in Offshore Wind Farms

Abstract: This paper presents a comprehensive investigation on high frequency (HF) switching transients due to energization of vacuum circuit breakers (VCBs) in offshore wind farms (OWFs). This research not only concerns the modeling of main components in collector grids of an OWF for transient analysis (including VCBs, wind turbine transformers (WTTs), submarine cables), but also compares the effectiveness between several mainstream switching overvoltage (SOV) protection methods and a new mitigation method called smart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The test results show that severe HF SOVs are induced on T G , when VCB G is switched off while WTG is connected. Thus, to reveal the mechanism for the occurrence of SOV in this scenario, and investigate the impact of system configurations on SOV, such as the length of submarine cable [13], the topology of the collector system [14], the setting of reactive power compensation capacity [15], and the arcing characteristic of VCB [16], a HF simulation model for an OWF is built in PSCAD/EMTDC. In the developed model, the voltage source is replaced by an ideal power grid with an infinite capacity.…”
Section: Accurate Modeling Of Offshore Wind Farmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The test results show that severe HF SOVs are induced on T G , when VCB G is switched off while WTG is connected. Thus, to reveal the mechanism for the occurrence of SOV in this scenario, and investigate the impact of system configurations on SOV, such as the length of submarine cable [13], the topology of the collector system [14], the setting of reactive power compensation capacity [15], and the arcing characteristic of VCB [16], a HF simulation model for an OWF is built in PSCAD/EMTDC. In the developed model, the voltage source is replaced by an ideal power grid with an infinite capacity.…”
Section: Accurate Modeling Of Offshore Wind Farmsmentioning
confidence: 99%
“…The parameters of the three-core submarine cable are set according to the actual geometric structure of the cable used in tests. The HF model of T G is designed with the method in [14], in which the inter-phase stray capacitance and the phase-to-ground capacitance under the HF state are considered. The solution time step in PSCAD is set 0.5 µs, and it is small enough to calculate SOVs, in which the HF component is around dozens of kilohertz.…”
Section: Accurate Modeling Of Offshore Wind Farmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HF current starts with a high rate of change that the VCB cannot turn off. However, with the attenuation of HF current, when the di/dt is less than a critical value when the current is crossing zero, the VCB will cut off HF current and turn it into a disconnected state, which is generally between 100-600 A/µs [24].…”
Section: Hf Arc Quenching Capabilitymentioning
confidence: 99%
“…It was found that the simulation results can be improved greatly if an appropriate VCB model was included in PSCAD, whereas little improvement was found in DigSILENT. Based on the above discoveries, the authors of [9][10][11][12][13] used a PSCAD/EMTDC simulation to calculate TOVs when VCBs were operated in different configurations, and the results showed that TOVs were affected by many factors, such as the operating scenarios of OWFs, the transformer locations, the cable length, and the wave propagations in the cables.…”
Section: Introductionmentioning
confidence: 99%